Incorporating Literacy in EFL Classroom: Teacher's Strategy and Students' Opinions: Teachers' Strategy And Students' Opinions - Musdalifa, Dinda Zachra; Nurchaerani, Meiyanti (Foremost Journal, 2021)
The aim of this study are to explore teachers’ strategy to teach literacy in EFL classroom and to find out their reflection in their literacy teaching. This study was conducted in descriptive qualitative approach, by using observation and interview to collect the data from the participants which were seven grades English teacher and ten students in seven grade in an Islamic private junior high school. The results showed that teachers applied various strategies to incorporate literacy in EFLclassrooom, They also shared students’ opinions as English teachers related to their belief and experience towards the teachers’ strategy and their effectiveness in teaching the literacy in English subject Keywords: Literacy, Strategies, EFL